Water as commons field stories - Foundation for Ecological Security (2023)
Foundation for Ecological Security 2022. Water as commons: Field stories (Understanding links between human actions and resource outcomes). PowerPoint presentation given during the Atal Bhujal Yojana Training, India, December 8, 2022